2017
DOI: 10.1016/j.ajur.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil-to-lymphocyte ratio predicts worse survival outcomes and advanced tumor staging in patients undergoing radical cystectomy for bladder cancer

Abstract: ObjectiveTo determine the role of neutrophil-to-lymphocyte ratio (NLR) in prognosticating survival outcomes in patients with advanced/metastatic urothelial bladder cancer.MethodsWe retrospectively reviewed 84 patients undergoing radical cystectomy (RC) for UCB from January 2002 to June 2012. NLR was computed (median: 5 days) prior to surgery. No patients received neoadjuvant chemotherapy. NLR was analyzed as a continuous variable and a cut-off point of 2.7 was obtained, with a statistical receiver operating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In our study an NLR >2.7 was also associated with poor OS, with a mean of 19.2 months vs 45.6 months (log rank test 0.03). Similar results were obtained by Tan et al (22.3 months vs 64.8 months) [ 31 ]. However, we could not define NLR as an independent prognostic factor for overall survival, as we obtained statistical significance only in univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…In our study an NLR >2.7 was also associated with poor OS, with a mean of 19.2 months vs 45.6 months (log rank test 0.03). Similar results were obtained by Tan et al (22.3 months vs 64.8 months) [ 31 ]. However, we could not define NLR as an independent prognostic factor for overall survival, as we obtained statistical significance only in univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Urothelial cancer patients with preoperatively increased NLR exhibited increased rates of disease recurrence after radical surgery compared to patients with lower NLR. Except for one publication by Mari et al, six articles included in this meta-analysis reported a statistically significant negative correlation of elevated NLR with RFS [ 20 , 21 , 22 , 32 , 33 , 36 , 45 ]. These results support the integration of NLR for risk stratification tools and could help guide decision-making, especially regarding treatment intensification.…”
Section: Discussionmentioning
confidence: 99%
“…Among advanced/metastatic bladder cancer patients, NLR could independently improve the prediction of survival outcomes. Higher NLR is strongly linked to a poorer OS, with a HR of 5.06 in one study and the CSS of 36% lower in another study [ 30 , 31 ]. The patients with an NLR of ≤3.0 are likely to have better cancer outcomes and attain greater survival improvement from chemotherapy compared to the group with NLR of >3.0.…”
Section: Discussionmentioning
confidence: 99%